Constructing social mobility and social cohesion within a business community in Malaysia - Abdullah, Azlina; Hassan, Nor Azlili; Ismail, Mohd Mahadee; Mohamad Zan, Ummi Munirah Syuhada; Mohd Noor, Mansor; Ahmad Shahabuddin, Faridatul Azna; Daud, Sity; Hassim, Ahmad Zul Hakimi (Human Resource Management Academic Research Society, 2018)
This paper discusses the social mobility within Malaysian business community, particularly in terms of the inter-generational social economic achievement, and its relationship with social cohesion. The survey was conducted on 554 business community and hawkers from various ethnics in Malaysia. The findings of the research showed that the intergenerational (father and children) education mobility is the upward mobility. The findings show that the level of social cohesion among business community is good due to the positive and moderate responds towards 18 social cohesion indicators based on 6 dimensions of social cohesion, namely self-belonging, recognition, inclusiveness, equality, participation and legitimacy. Study on social mobility and social cohesion is very significant because the social cohesion can only be succeeding when individuals in the community believe that they are able to improve their quality of life and their children will enjoy the happiness through their own abilities, talents and efforts. Thus, when a society enjoyed a convenience life, not separated in any social economic matters, have the same rights to change their lives and acquire the equal rewards, then the society can be considered to be stated at the level of social cohesion.